La Camargue, terre d’enjeux, première étape d’une gestion intégrée des zones côtières - Hugues Heurtefeux; Provence Lanzellotti (VertigO)
In the 19th century, the expression “empty land ” applied extremely well to Camargue land ; in the 20th century that of “littoral of seizure” (territoire d’empoigne)” replaced it easily. The objective is to reconcile on this land, in integrated coastal zone management reasoning, the conservation of nature, landscape and traditions with tourism activities. It is thus absolutely necessary to prevent a "Coastal squeeze" on this emblematic land which would lead to less beach and more sprawl of concrete (groynes, hard rocks to hold the line). In this perspective, we will see how strategic principles of the coastal management were defined at the request of the Camargue Regional Natural Park. The original reasoning is founded on the governorship: all the identified local actors have been met during bilateral interviews. The synthesis of these interviews made it possible to draw up a list of strategic principles, discussed, amended and validated by the totality of the local actors gathered within a steering committee. All this process genesis stages are developed, examined and analyzed.